Universal identification of lethal amanitas by using Hyperbranched rolling circle amplification based on α-amanitin gene sequences. (15th November 2019) - He, Zhengmi; Luo, Tao; Fan, Fengxia; Zhang, Ping; Chen, Zuohong
Highlights: Universal identification of lethal amanitas was established using a HRCA method. All lethal Amanita species produced positive HRCA reactions. HRCA sensitivity was 100-fold higher than conventional PCR. Positive results could be visualized using a coloration reaction. Abstract: Hyperbranched rolling circle amplification (HRCA) with a padlock probe (PLP) targeting the α-amanitin ( α-AMA ) gene, as a screening tool for the universal identification of lethal amanitas, was established in this study. With the isothermal HRCA assay, all of the lethal Amanita species tested from Phalloideae (10) were positive, while the non- Phalloideae Amanita species (15) and three amanitin-containing Lepiota and Galerina species were negative. Furthermore, the PLP based on α-AMA sequences from lethal Amanita species was effective for Amanita α-AMA, but not Amanita β-AMA or non- Amanita α-AMA . HRCA sensitivity was 100-fold higher than conventional PCR with a detection limit of 100 copies (recombinant plasmid containing α-AMA ), and 0.2% lethal amanitas could be detected in dry mushroom blends. The HRCA method presented provided a rapid, specific, sensitive and low-cost identification tool for lethal amanitas.